WOmen's Action for Mums and Bubs (WOMB) Trial Protocol: A Non-randomized Stepped Wedge Implementation Trial of Participatory Women's Groups to Improve the Health of Aboriginal and Torres Strait Islander Mothers and Children in Australia - Carlisle, Karen; Felton-Busch, Catrina; Cadet-James, Yvonne; Taylor, Judy; Bailie, Ross; Farmer, Jane; Passey, Megan; Matthews, Veronica; Callander, Emily; Evans, Rebecca; Kelly, Janet; Preston, Robyn; et al. (Frontiers in Public Health, 2020)
Introduction: In Australia, there have been improvements in Aboriginal and Torres Strait Islander maternal health, however inequities remain. There is increasing international evidence illustrating the effectiveness of Participatory Women’s Groups (PWGs) in improving Maternal and Child Health (MCH) outcomes. Using a non-randomised, cluster stepped-wedge implementation of a complex intervention with mixed methods evaluation, this study aims to test the effectiveness of PWGs in improving MCH within Indigenous primary care settings in Australia and how they operate in various contexts. Methods: This study takes place in ten primary health care services across Australia and involves the recruitment of existing PWGs or the setting up of new PWGs. Services are paired based on geography for practical reasons and two services commence the PWG intervention at three monthly intervals, with the initial four services being those with existing women’s groups. Implementation of the PWGs as an intervention involves training local facilitators of PWG groups, supported engagement with local MCH data through workshops, PWGs identifying and prioritising issues and strengths and co-implementing solutions with health services. Outcomes are measured with yearly MCH audits, a cost-effectiveness study, and process evaluation of community participation and empowerment. Discussion: This study is the first to formally implement and quantitatively, yet with contextual awareness, measure the effect of applying a community participation intervention to improve the quality of Aboriginal and Torres Strait Islander MCH in Australia. Findings from this work, including detailed theory-producing qualitative analysis, will produce new knowledge of how to facilitate improved quality of MCH care in Indigenous PHC settings and how to best engage community in driving health care improvements. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12618000945224 Web address: http://www.ANZCTR.org.au/ACTRN12618000945224.aspx